КРОССФИТ КАК ЭФФЕКТИВНАЯ СИСТЕМА СПОРТИВНО-ОРГАНИЗОВАННОГО ФИЗИЧЕСКОГО СОВЕРШЕНСТВОВАНИЯ СЛУШАТЕЛЕЙ АКАДЕМИИ МВД РЕСПУБЛИКИ УЗБЕКИСТАН - Кошбахтиев, И.А.; Кочкаров, А.А.; Умурзаков, Б.Б. (SCIENCE and SOCIETY, 2016)
The article considers the legitimacy of application of crossfit in the system of physical training of the students of the 3 and 4 courses of the Academy of the MIA of the Republic of Uzbekistan.
Keywords: physical training; educational process; crossfit; perfection of physical training of the students